Cytopathology of Extragenital Transmissible Venereal Tumour in a Dog - Jadhao, Abhilash; Baba, Omer K.; Gupta, Kuldip (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Transmissible Venereal Tumour (TVT) is a horizontally transmitted tumor of dogs, also known as canine transmissible venereal sarcoma, venereal granuloma, transmissible lymphosarcoma, or sticker tumor of mesenchymal origin (Saravanan et al., 2015). TVT can easily transmit from animal to animal during copulation by viable tumor cells by licking, biting, and by direct contact with the tumor and frequently affects dogs of either sex (Sritrakoon et al., 2020). TVT occasionally affects internal genitalia and extragenital sites such as skin, mouth, eye, nasal and other sites too (Gupta and Sood, 2012; Saravanan et al., 2015; Sritrakoon et al., 2020 and Dhillon et al., 2021). TVT is distinguished morphologically into three cytomorphological types: (1) Lymphocytic type, having granular cytoplasm with centrally placed nucleus and intracytoplasmic vacuoles. (2) Plasmocytic type, having eccentric nuclei with many cytoplasmic vacuoles, and (3) Mixed type, characterized by both lymphocytic and plasmacytic types (Florez et al., 2016). The histological features of TVT resemble histiocytoma, whereas in the cytology of TVT, cytoplasm reveals punctuate vacuoles in most cells that differ from histiocytic tumor and other round tumor cells (Abeka, 2019). The present case report deals with the hematobiochemical, cytological, and histopathological findings in an unusual case of extragenital TVT in a dog.